Dampak Branding Ingridient dan Gaya Hidup Terhadap Keputusan Pembelian Konsumen Skintific di Desa Bintang Bayu - Anggraini, Widya Fitri; Amelia, Wan Rizca (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of branding ingredients and lifestyle on consumers' purchasing decisions for Skintific skincare products in Bintang Bayu Village. The research method used is a quantitative approach with a survey technique. Data were collected through questionnaires distributed to 92 respondents. Data analysis was conducted using multiple linear regression with SPSS 27. The results show that branding ingredients and lifestyle have a positive and significant effect on consumer purchasing decisions. Branding ingredients enhance perceived quality and trust in the product, while lifestyle plays a role in shaping consumer preferences and consumption patterns. Therefore, marketing strategies that emphasize branding ingredients aligned with the target consumer's lifestyle can increase brand competitiveness in the skincare market